Ultrasound-Controlled Manual Magnet Repositioning in Magnet Dislocation of Cochlear Implants - Rupp, Robin; Hornung, Joachim; Balk, Matthias; Traxdorf, Maximilian; Sievert, Matti; Hoppe, Ulrich; Iro, Heinrich; Gostian, Antoniu Oreste (Otology & Neurotology, 2021)
OBJECTIVE: To investigate whether ultrasound is a helpful and reliable diagnostic tool to survey the status of the magnet previous and after manual repositioning in patients with partially dislocated cochlear implant (CI) magnets and to assess the success rate of a manual repositioning maneuver. DESIGN: A prospective cohort study. SETTING: A tertiary referral medical center. PATIENTS: Patients with a cochlear implant who presented with magnet dislocation after magnetic resonance imaging (MRI) between June 1, 2019 and July 15, 2020. INTERVENTIONS: Manual repositioning of the partially dislocated CI magnet surveyed by pre- and post-interventional ultrasound. MAIN OUTCOME MEASURES: Rate of successfully diagnosed and manually repositioned magnets; complication rate and recurrence rate after initial manual repositioning maneuver. RESULTS: Nine patients presented with a partial magnet dislocation diagnosed by pre-interventional ultrasound following MRI (n = 9 magnets; three ♀; eight right-sided implants; 65.4 ± 21.7 yr). All magnets were repositioned manually. The magnets were successfully repositioned at the first attempt in six out of eight patients. Two patients required a second and one patient a third attempt of manual repositioning. Post-interventional ultrasound confirmed the entirely restored magnet position in all cases. During the mean follow-up period of 7.3 months (±5.4 mo) no patient experienced any complication or recurrent dislocation of the respective magnet. CONCLUSION: Manual magnet repositioning is a feasible and reliable method with a high success rate for partially dislocated CI magnets. The pre-interventional diagnosis as well as the post-interventional confirmation of the magnet status can be effectively determined by ultrasound. Thus, manual magnet repositioning and ultrasound investigation can be advocated as first-line therapeutic and diagnostic instruments when dealing with partial magnet dislocation.
CRIS-Team Scopus Importer:2021-06-04